Support of metrological traceability of capacitance measurements in Ukraine - Velychko, Oleh; Shevkun, Sergii (Eastern-European Journal of Enterprise Technologies, 2017)
The comparative analysis of the results of the RMO international key and supplementary comparisons of national standards of units of electrical capacitance is conducted with the aim of evaluation of convergence. For the comparisons, the reference values with the expanded uncertainties are calculated and the degrees of equivalence of standards of participants and expanded uncertainties for the nominal values of measures of 10 pF and 100 pF on frequencies of 1 kHz and 1.592 kHz are determined. Metrological traceability of the national standard of every participant of comparisons to the units of the International system of units SI is determined. For verification of consistency of the results of comparisons, the values of the χ2 criterion for the results of comparisons of standards of participants taking into account the measurement uncertainty are calculated. The obtained values of the criterion of consistency for the participants can be considered consistent, which is the objective confirmation of the measurement uncertainties declared by the participants. The evaluation of calibration and measurement capabilities of Ukraine for the unit of electrical capacitance is realized. The methodology of evaluation of measurement uncertainty in the wide range of capacitance values (from 10 pF to 10 nF) is proposed. The results the calculations of the values of measurement uncertainties according to the proposed methodology revealed that the results correspond to the data published in the international key comparison database for Ukraine in the range of capacitance values from 10 pF to 10 nF on frequencies of 1 kHz and 1.592 kHz.